2012
DOI: 10.1002/mrm.24190
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized 129Xe gas lung MRI–SNR and T2* comparisons at 1.5 T and 3 T

Abstract: In this study, the signal-to-noise ratio of hyperpolarized (129)Xe human lung magnetic resonance imaging was compared at 1.5 T and 3 T. Experiments were performed at both B(0) fields with quadrature double Helmholtz transmit-receive chest coils of the same geometry with the same subject loads. Differences in sensitivity between the two field strengths were assessed from the signal-to-noise ratio of multi-slice 2D (129)Xe ventilation lung images obtained at the two field strengths with a spatial resolution of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…For example, Xu et al (16) reported mean SNR of 36, and 44 for 129 Xe ventilation MRI at 1.5 T and 3.0 T. They employed a voxel volume of 0.24 ml and an estimated DE ∼0.36 ml. This suggests that they achieved an SNR n of 4.2 ml -2 at 1.5 T, and 5.0 ml -2 at 3.0 T. Even after accounting for their use of a lower 4 kHz bandwidth, their normalized SNR values are 50-86% higher than those we report here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xu et al (16) reported mean SNR of 36, and 44 for 129 Xe ventilation MRI at 1.5 T and 3.0 T. They employed a voxel volume of 0.24 ml and an estimated DE ∼0.36 ml. This suggests that they achieved an SNR n of 4.2 ml -2 at 1.5 T, and 5.0 ml -2 at 3.0 T. Even after accounting for their use of a lower 4 kHz bandwidth, their normalized SNR values are 50-86% higher than those we report here.…”
Section: Discussionmentioning
confidence: 99%
“…However, this slope was much smaller or even presented as a descending trend in the GRE acquisition (Figure 6). This is likely because GRE images were acquired from the anterior-to-posterior slice order, which attenuates the true signal enhancement in the better-ventilated posterior slices because they experience greater T1 and RF decay before being encoded (16,34). By contrast the 3D-radial acquisition is a truly 3D scan that preserves the physiologically dictated SNR distribution.…”
Section: Discussionmentioning
confidence: 99%
“…NAXe MR is particularly promising at 3 T, wherein the increased SNR compared with 1.5 T—arising from a combination of differences in Larmor frequency, field inhomogeneity, coil sensitivity and the “system” (e.g., transmission line and receiver noise figure) at the two field strengths—reflects previous observations with spoiled gradient echo imaging . This SNR benefit, coupled with the possibility of using receiver array coils rather than standard transmit–receive designs as applied here, may facilitate NAXe lung imaging with 3D isotropic resolutions in future.…”
Section: Discussionmentioning
confidence: 99%
“…The T 2, CPMG of 129 Xe at 1.5 T or 3 T has not been reported, although measurements at low‐field (0.2 T) in humans , and high‐field (4.7 T) in rats have suggested a value of ∼300 ms in the lungs. However, because the field dependence of T 2, CPMG is not known, and measurement of this parameter is challenging in the lungs with xenon due to the finite inter‐echo times attainable and diffusion of the gas causing incomplete refocusing, a range of T 2, CPMG values between 300 ms and 25 ms (the 129 Xe T 2 * in partially inflated human lungs at 1.5 T ) was considered in the following simulations. The longitudinal relaxation time of 129 Xe in human lungs was taken to be T 1 = 20 s .…”
Section: Methodsmentioning
confidence: 99%
“…Note that, for this work, TE 90 values were measured from the center of the RF pulse, rather than from its end; thus, TE 90 values presented here are longer than those indicated previously). The dissolved‐phase components were back extrapolated to t = 0, using T2* = 2 ms, whereas the gas‐phase was corrected to t = 0 using T2* = 50 ms . In addition, the 129 Xe gas‐phase image intensity was increased by sin(20°)/sin(0.5°) = 39 to account for the higher flip angle applied to the dissolved versus gas‐phase images.…”
Section: Methodsmentioning
confidence: 99%